Village Government Challenges Facing Technological Advances: Readiness for the digital era in Bengkalis Village, Riau Province, Indonesia - Andriyus, Andriyus; Yuslaini, Nina; Shiddiqy, Muhammad Arsy Ash; Safitri, Bella Hidiyan (Kemudi, 2024)
This study aims to analyse the readiness of the village government in facing the digitalisation era seen from various aspects to analyse the problems and obstacles of the village government in facing the digitalisation era. The method used is descriptive qualitative to explore in depth empirical phenomena. The results showed that the village government in Bengkalis Regency was not ready to face the digitalisation era from the aspect of human resources, the knowledge and skills of village officials were still low in mastering technology and information and the readiness of technological infrastructure that had not been able to support the digitalisation era, namely the uneven internet network in all villages. The conclusion of this research is that the village government in Bengkalis Regency does not have qualified readiness in facing the digitalisation era.